Long COVID? Prospects for economic scarring from the pandemic. (12th November 2022) - Barrett, Philip; Das, Sonali; Magistretti, Giacomo; Pugacheva, Evgenia; Wingender, Philippe
Abstract: This paper examines the potential persistent effects (scarring) of the COVID‐19 pandemic on the economy and the channels through which they may occur. Our findings from a broad set of historical recessions confirm that recessions are associated with persistent output losses and that the greatest scarring has occurred following financial crises. The amount of scarring following pandemic and epidemic recessions in the sample is in between that of typical recessions and financial crises. Results on the channels show that the productivity channel is important, as all types of recessions have been followed by persistent losses to total factor productivity.